2010
DOI: 10.1038/onc.2010.474
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 subverts p63 control over KLF4 expression in keratinocytes

Abstract: Genetic experiments established that p63 is crucial for the development and maintenance of pluri-stratified epithelia and KLF4 for the barrier function of the skin. KLF4 is one of the factors that reprogram differentiated cells to iPS. We investigated the relationship between p63 and KLF4 using RNA interference, overexpression, chromatin immunoprecipitation and transient transfections with reporter constructs. We find that p63 directly represses KLF4 in normal keratinocytes (KCs) by binding to upstream promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 72 publications
3
35
1
Order By: Relevance
“…We previously observed that ΔNp63 expression, the predominant isoform of Trp63 in epidermis (Melino, 2011), was reduced in oral epithelia of K5-GR transgenic mice, suggesting negative regulation by GR (Cascallana et al, 2005). Importantly, ΔNp63 represses Klf4 expression by directly binding its promoter (Cordani et al, 2011), and the expression of both TFs is mutually exclusive in the epidermis, with ΔNp63 having the highest expression basally and Klf4 suprabasally. We first evaluated whether GR could regulate Klf4 indirectly by modulating Trp63 expression, by testing whether Trp63 isoform levels were affected by Dex in control and GR EKO cell lines (Fig.…”
Section: Gr Negatively Regulates Trp63 Isoforms In Keratinocytesmentioning
confidence: 94%
“…We previously observed that ΔNp63 expression, the predominant isoform of Trp63 in epidermis (Melino, 2011), was reduced in oral epithelia of K5-GR transgenic mice, suggesting negative regulation by GR (Cascallana et al, 2005). Importantly, ΔNp63 represses Klf4 expression by directly binding its promoter (Cordani et al, 2011), and the expression of both TFs is mutually exclusive in the epidermis, with ΔNp63 having the highest expression basally and Klf4 suprabasally. We first evaluated whether GR could regulate Klf4 indirectly by modulating Trp63 expression, by testing whether Trp63 isoform levels were affected by Dex in control and GR EKO cell lines (Fig.…”
Section: Gr Negatively Regulates Trp63 Isoforms In Keratinocytesmentioning
confidence: 94%
“…In skin, DNp63 and Klf4 are expressed in opposite compartments in the basal and superficial layers of the epidermis, respectively, likely because p63 directly binds to the Klf4 promoter and represses it. 53,54 Thus, p63 À / À MEFs might in fact be expected to have increased levels and/ or activity of endogenous Klf4, and as a result enhanced OK reprogramming efficiency because of additive effects of endogenous and exogenous Klf4. Indeed, we found that two out of four MET markers were upregulated in p63 À / À MEFs during OK reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, p63 has been shown to directly repress KLF4, a major factor that reprograms differentiated cells into iPS by binding to an upstream promoter site. 116 Indeed, the epidermis shows a mutually exclusive expression of DNp63 and KLF4. Of interest for this discussion, however, is the evidence that mutant p53 counteracts the action of DNp63 on KLF4 expression, suggesting that p63 and KLF4 are not only relevant in the growth-promoting effect of p63 in keratinocytes, but also in the tumor-predisposing p53 mutations which, by hijacking p63, results in KLF4 dysregulation.…”
Section: Np63mentioning
confidence: 99%